Influence of academic-professional hardiness on the subjective well-being of students in socionomic professions - E. A. Shmeleva; P. A. Kislyakov; I.-L. S. Meyerson; T. K. Phan (Russian State Vocational Pedagogical University, 2023)
Introduction. Professions such as doctors, teachers, psychologists, and social workers entail a certain risk to the psychological well-being of both professionals and students due to their educational and professional activities.Aim. The present study aims to explore the factors, which contribute to the development of resilience skills in students of socionomic professions, and which could ensure their psychological well-being in relation to their future professional activities.Methodology and research methods. The theoretical foundations of resilience theory by S. Maddi, D. A. Leontiev, E. I. Rasskazova and others served as subject-scientific guidelines, as well as the approaches of positive psychology to studying subjective well-being of individuals (K. Rogers, M. Seligman). Psychodiagnostic methods such as "Academical-Professional Hardiness", "Subjective Well-Being Scale", and "Coping with Stress Questionnaire" (COPE) were employed. The collected data were processed using descriptive statistics, correlation analysis, regression analysis, and confirmatory factor analysis. Research participants. The sample consisted of students majoring in pedagogy, psychology, medicine, and social sciences. The total number of participants was 282, ranging in age from 18 to 20 years old.Results and scientific novelty. The results allow refining knowledge about the characteristics of psychological factors, which contribute to the subjective well-being of students in helping professions. It has been found that the main predictors of subjective well-being among students in socionomic fields of study are academic and professional hardiness, as well as constructive coping styles in dealing with difficulties. Additionally, differentiation in the choice of dominant constructive coping strategies has been observed among students from different academic fields.Practical significance. The obtained results allow refining the understanding of educational and professional resilience as a predictor of students' psychological well-being in helping professions through productive coping styles, as well as outlining approaches to developing and implementing programmes for enhancing academic and professional hardiness among students in socionomic fields of education (such as pedagogy and education, psychology, social work, medicine). The theoretical and empirical findings of this research can be useful in designing lessons on psychological disciplines.